A 14-year study on ceramic waste slag-based lightweight aggregate concrete. (2nd May 2022) - Liang, Yuhang; Wang, Qing; Gan, Wei; Liao, Jinlong; Lai, Mianheng; Ho, Johnny
Highlights: Ceramic waste slag-based lightweight aggregate services well after 14 years' curing. Chloride ion permeability level of 14-year-old LWAC is very low. Enhanced interfacial transition zone is observed in LWAC with CLWA. Consuming ceramic waste slag in LWAC is feasible and effective. Abstract: Lightweight aggregate concrete (LWAC) characterized with low dead weight and high performance, has been applied widely in concrete structures in the past two decades. Mostly, LWAC components play a crucial role in reducing structural weight and keeping structures in good service condition. However, long-term properties of LWAC, especially those prepared with industrial waste-based aggregate, directly affect the durability of structure but have not been explored yet. In the present study, 14-year LWAC incorporating with ceramic waste-based lightweight aggregate (CLWA) were experimentally studied. Traditional LWAC with furnace slag lightweight aggregate (FLWA) was designed as a contrast. Properties of 14-year LWAC such as compressive strength, chloride ion permeability, X-ray diffraction and open porosity were evaluated. In addition, high magnification electron microscope, scanning electron microscope and energy dispersive spectroscopy (SEM-EDS) were adopted to characterize the interfacial transition zone (ITZ) and microstructure of LWAC. Results indicates that after 14 years' curing, no strength reduction is detected and the chloride ion permeability maintains in very low level for LWAC. Long-term performance of LWAC with CLWA is superior to that with FLWA, thanks to the disconnected uniform pores/rough particle surface distributed in CLWA and the compact ITZ between aggregates and mortar.